SPECTRAL ANALYSIS OF FM SIGNALS USING SDR FOR THE HIGH-TECH SOCIETY - Tamayo Suárez, Felipe Juglar (Telemática, 2020)
In this article, the frequency-modulated signals have been analyzed in the spectrum, with the aim of reviewing the performance of these systems to guarantee the quality of the service in the Radiocuba company. The NooElec NESDR Nano 2-Tiny Black RTL-SDR USB Set device (RTL2832U + R820T2) has been used to analyze the levels of field strength, characteristic that defines the composition of the stereo FM sign in the transmission, the frequency deviation in the modulation, the situation of guard band, adjacent channel interference and co-channel interference. Have been shown features of the FM sign and the SDR technology that help to understand these systems. Using the TVSharp software with the same device, the analogical television video signal has been visualized, observing that the development of the software reached until today, has introduced new benefits for the configuration of this same hardware element, which facilitated the verification of signals from analogical television, which was not conceived in the original design of the device. The audio corresponding to the analog video of each channel is demodulated, using the SDR Console v3.0.7 software. The power spectral density has been observed at the known frequency of a digital transmitter, although the device did not provide digital television-DTMB signals without modulating. This document offers a perspective of the meaning that acquires the information in society through the employment of SDR like an accessible option to analyze situations that many times require very expensive equipment.